PEMANFAATAN HERBAL VAGINA PRACTICE DALAM BUDAYA WANITA MADURA TERHADAP FLORA NORMAL VAGINA - Dian Eka Januriwasti; Enggal Sari Maduratna (NHM PRESS, 2021)
The tradition of the palace as the cultural center of Javanese society also keeps various recipes for traditional medicine. Beauty care for women is also a court tradition which is still developing in modern society, including the traditional treatment of female intimate organs. Treatments or practices related to the female sex organs are known as Vaginal Practice.This research uses a qualitative approach. The locations chosen were all districts on Madura Island including Bangkalan, Sampang, Pamekasan, and Sumenep Regencies. The selection of the research sample used a non-random technique, namely snowball sampling.Result of research 100 respondents consumed herbal medicine as a form of vaginal treatment, and 79 respondents used hundred as a form of vaginal treatment. There were 30 women who routinely consumed herbal medicine experienced bacterio vaginosis, while 7 women who used hundreds experienced bacterio vaginosis.The existence of a tradition that cannot be eliminated in the behavior of the Madurese community should get attention from health workers regarding the methods and combinations of treatment that are less safe so far in the practice of vaginal care with the use of herbs